Precision compatibilizers for composites: in-between self-aggregation, surfaces recognition and interface stabilization. Issue 11 (1st March 2018) - Samsoninkova, V.; Venkatareddy, N. L.; Wagermaier, W.; Dallmann, A.; Börner, H. G.
Abstract : Peptide–polymer conjugates are applied as precision interface-stabilizers in hybrid-materials. Besides surface–peptide interactions also peptide–peptide interactions determine solubility and availability of stabilizers at internal interfaces. Abstract : Peptide–polymer conjugates are applied as interface stabilizers that are precisely tuned to recognize the surfaces of inorganic constituents in composites. A set of peptide sequences is usually selected through phage-display and a strategy is presented for the identification of the most effective sequences through the evaluation of secondary interactions, including not only surface binding but also solubility and self-aggregation tendency.